2007
DOI: 10.1111/j.1600-0838.2007.00706.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of eight weeks of endurance exercise training on right and left ventricular volume and mass in untrained obese subjects: a longitudinal MRI study

Abstract: The aim of the present investigation was to examine how 8 weeks of intense endurance training influenced right and left ventricular volumes and mass in obese untrained subjects. Ten overweight subjects (19-47 years; body mass index of 34+/-5 kg/m(2)) underwent intensive endurance training (rowing) three times 30 min/week for 8 weeks at a relative intensity of 72+/-8% of their maximal heart rate response (mean+/-SD). Before and after 8 weeks of endurance training, the left and the right end-diastolic volume (ED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 37 publications
1
14
1
Order By: Relevance
“…8,11,46 Longitudinal cMRI studies confirmed that eccentric ventricular remodeling is inducible in previously sedentary younger individuals with moderate- to high-intensity endurance training over relatively brief periods of time. 18,47,48 …”
Section: Discussionmentioning
confidence: 99%
“…8,11,46 Longitudinal cMRI studies confirmed that eccentric ventricular remodeling is inducible in previously sedentary younger individuals with moderate- to high-intensity endurance training over relatively brief periods of time. 18,47,48 …”
Section: Discussionmentioning
confidence: 99%
“…This fi nding corresponds to results from echocardiographic ( 29,36 ) and MR imaging ( 24 ) studies that showed that even dramatic changes in training loads do not infl uence this index of integrated ventricular systolic function at rest. It has been reported that structural changes of the heart in athletes also involve the right ventricle, leading to higher RV stroke volume, end-diastolic volume, and myocardial mass ( 24,37 ). In our study, there were no differences in the LV-to-RV ratios of these volume and mass indexes, showing that the benign adaptive structural and functional changes with triathlon training associated with athlete's heart represent a balanced cardiac hypertrophy with regulative enlargement of all chambers ( 23 ).…”
Section: Cardiac Imaging: Cardiac Adaptations In Elite Triathletesmentioning
confidence: 99%
“…CMR imaging is considered the current reference standard for the evaluation of left ventricular (LV) and right ventricular (RV) cardiac volume and mass, allowing for detection of smaller changes than other imaging modalities. 8 Most previous studies focused only on specific aspects of cardiac adaptation, for example, LV or RV hypertrophy, 7,9 assessment of myocardial strain, 10 or evaluation of cardiac fibrosis with late gadolinium enhancement (LGE). 11 There is still controversy whether besides beneficial cardiovascular adaptation 12,13 there might be adverse cardiac effects 14 of high-intensity endurance training.…”
Section: See Clinical Perspectivementioning
confidence: 99%